Improving Quality of Life in Type II Diabetes Through Self-Care and Family Support - Florien Nisak; Idrawati Bahar; Verra Widhi Astuti,; Netti; Yessi Fadriyanti (CV. CENDIKIA JENIUS INDONESIA, 2025)
Background: Global and national data indicate an increasing trend in diabetes mellitus (DM) cases, including in Padang City, where the Belimbing Community Health Center recorded the highest number of type II DM patients in 2023. Several previous studies have reported a low quality of life among patients, prompting this study to explore similar trends and serve as a basis for future improvements. This study aims to examine the relationship between self-care and family support and the quality of life of patients with type II diabetes in the working area of the Belimbing Community Health Center. Methods: This quantitative, cross-sectional study was conducted from December to June 2025. The population included 468 type II DM patients treated at the health center between August and October. A total of 88 respondents were selected through cluster random sampling. Data were collected using the SDSCA, HDFSS, and WHOQOL-BREF questionnaires, and analyzed using univariate and bivariate analysis with the Chi-Square test. Results: The findings showed that 47.7% of patients had poor self-care, 15.9% received insufficient family support, and 50.0% had a poor quality of life. A significant relationship was found between self-care (p = 0.00) and family support (p = 0.001) and the quality of life of patients. Conclusion: Community health centers are encouraged to organize productive community-based activities and provide education and informational media to families in order to support patient care and enhance self-care management.